Petri Net Decomposition Approach for Bi-Objective Routing for AGV Systems Minimizing Total Traveling Time and Equalizing Delivery Time - Shuhei EDA; Tatsushi NISHI; Toshisada MARIYAMA; Satomi KATAOKA; Kazuya SHODA; Katsuhiko MATSUMURA (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2012)
In this paper, we propose Petri net decomposition approach for bi-objective optimization of conflict-free routing for AGV systems. The objective is minimizing total traveling time and equalizing delivery time simultaneously. The dispatching and conflict-free routing problem for AGVs is represented as a bi-objective optimal firing sequence problem for Petri Net. A Petri net decomposition approach is proposed to solve the bi-objective optimization problem efficiently. The convergence of the proposed algorithm is improved reducing search region by the proposed coordination method. The effectiveness of the proposed method is compared with that of a nearest neighborhood dispatching method. Computational results are provided to show the effectiveness of the proposed method.